Research on the Influence Law of Vibration on Grade G Cement - Niu, Manli; Wu, Xinyuan (International Journal of Mechanical and Electrical Engineering, 2025)
The paper investigates the effect of vibration on compressive strength and cementitious strength of cement stone through experiments, analyzes the effect of different vibration parameters on the macroscopic mechanical properties of cement, and microscopically, it is observed by electron microscope to verify the effect of vibration on cement stone to improve the internal structure of cement stone, and the experimental results show that vibration is able to significantly improve the compressive strength and cementitious strength of cement stone. Within a certain range, with the increase of vibration frequency and time, the compressive strength gradually increases, while the cement strength shows a trend of increasing first and then stabilizing. It is found that vibration can promote a more uniform distribution of cement particles, reduce the number and size of pores, vibration 20Hz, 40Hz and 60Hz compared with the porosity of static cement reduced by 23.14%, 39.72% and 50.79%, improving the compactness of cement stone. Guidelines are provided for the selection of optimal vibration parameters for vibratory cementing tool operations.